Base station and notification method - TAKAHASHI HIDEAKI; HAPSARI WURI ANDARMAWANTI; UCHINO TOORU (2018)
Provided is a base station in a wireless communication system capable of handling carrier aggregation, the base station comprising: a reception unit which receives from a user device first band combination information which indicates a band combination that the user device can handle with carrier aggregation, the first band combination information being generated in a first format; a generation unit which generates second band combination information using a second format on the basis of the band combination indicated by the first band combination information; and a transmission unit which transmits the second band combination information generated by the generation unit to another base station different from the subject base station or an exchange device. 提供种基站，是支持载波聚合的无线通信系统中的基站，其具有：接收单元，从用户装置接收表示所述用户装置通过载波聚合能够支持的带域的组合且以第格式生成的第带域组合信息；生成单元，基于所述第带域组合信息所示的带域的组合，使用第二格式来生成第二带域组合信息；以及发送单元，将由所述生成单元生成的所述第二带域组合信息发送给与该基站不同的其他基站或交换机。